Study and Analysis of the Structural and Magnetic Properties of Nickel Iron Substituted with Different Proportions of Cerium - Hassan N. Mahmood, Khalid H. Razeg, Sabah M. Ali Ridha, (Pakistan Journal of Medical & Health Sciences, 2023)
Magnetic nanoferrites were prepared from nickel substituted with pure cerium ions by the following formula, NiCexFe2-xO4, where (x = 0.00, 0.02, 0.06, 0.08, 0.1) and in different proportions and weights using the chemical sol-gel method, after which it was calcined at 600, 800, and 1000 °C. And by using different characterization methods to examine the prepared powders such as X-ray diffractometer (XRD), scanning electron microscopy (FESEM) and vibration sample magnetometer (VSM). The X-ray diffraction patterns of the prepared samples confirmed the formation of single-phase soft magnetic nanoparticles of spinel nature and measured the particle size by XRD and FESEM analysis. Through, EDS analysis it was confirmed that there are no extra impurities and that the samples are pure. The VSM technique was used to analyze the magnetic properties of the as-prepared composites, and the saturation magnetization (Ms) and coercivity (Hc) decreased with increasing concentration of compensated cerium ions. These properties reveal the highly magnetic nature of cerium-substituted nickel nanoparticles and their potential for use in modern communication technology. Keywords: Nanoparticles, Nickel ferrites, cerium ion, X-ray diffraction, FESEM analysis, VSM analysis.